Financial and economic viability analysis of baru almond (Dipteryx alata Vogel) agroextractivism in the Urucuia River Valley, Arinos/MG (Sustainability in Debate, 2024)
The baru tree (Dipteryx alata) plays a vital role in the conservation of the Brazilian Cerrado. Its almonds are highly valued for their nutritional content and the increasing demand for sociobiodiversity products, generating income for agroextractivists. This study analyses the viability of baru extractivism in the Urucuia River Valley, Arinos/MG. Financial and economic data were collected from the 2013-2014 harvests through semi-structured interviews. Costs, revenues, and cash flow were calculated based on production volatility in different scenarios. The results indicated that extractivism is financially viable in most profitability indicators, except for medium-scale agroextractivists in the 2014 harvest, due to increased labour costs. The simulation of economic viability over 10 years, including investments, showed that extractivism is viable only in scenarios involving the association of agroextractivists. Therefore, cooperation and community organisation strategies are essential for the viability of baru extractivism.